Kelengkapan Pengisian Informed Consent Pada Delinguent Medical Record Pasien Rawat Inap Di RS X Jakarta - Rianta Sari Gultom; Laela Indawati; Deasy Rosmala Dewi; Nanda Aula Romana (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2022)
Informed consent is the consent that a patient gives to a doctor to perform a medical action after the patient receives a complete and understood explanation of the medical action. The purpose of this study is to find out the completeness of filling informed consent of inpatients at Hospital X South Jakarta, the type of research used is quantitative descriptive with a population of 353 and a sample of 78 inpatient medical records in the period October-December 2020. The method of data collection is Observation and Interview, following the results of research that has been conducted at Hospital X South Jakarta on 78 medical records known percentage average value based on 4 components, namely completeness 82% and incomplete 18%. Filling of patient identification components averages the percentage of completeness (89%), completeness of filling important report components 90%, completeness of filling the author authentication component (73%), completeness of filling of good note components (63%). Factors causing the incompleteness of informed consent are, the absence of standards of special operational procedures governing the filling of informed consent, doctors and nurses are busy due to the number of patients so that it is not fully filled, and the number of patients who do not have or bring witnesses / families when going to approve medical actions, this makes incompleteness in informed consent. With this, it is expected that the creation of SPO and socialization about filling the completeness of informed consent to be improved again.